2010
DOI: 10.1089/jop.2009.0111
|View full text |Cite
|
Sign up to set email alerts
|

Handling Test of Eye Drop Dispenser—Comparison of Unit-Dose Pipettes with Conventional Eye Drop Bottles

Abstract: Purpose: The aims of this study were to investigate how elderly people handle single-use eye drop dispensers (unit-dose pipettes) and to compare the performance with conventional eye drop bottles. Methods:In this open-label study, the handling of unit-dose pipettes and conventional eye drop bottles was compared in 41 elderly people who had little or no prior regular use of eye drop dispensers. The participants tested both types of dispenser once, and the following 7 variables were studied: ease/difficulty of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Page 35 reported significantly more failures among women than men because of differences in grip strength. Finally, Parkkari et al 45 presented statistically significant differences (P = 0.0025) in ease of opening reported by men and women. Decreased cognitive function, as measured by the Mini-Mental-State Examination (MMSE), 30,32,40 and cognitive interpretation 31,35 impacted in a decreased ability to open medicine containers.…”
Section: Research Stream Onephysical Functionality and User Capabilitymentioning
confidence: 91%
See 3 more Smart Citations
“…Page 35 reported significantly more failures among women than men because of differences in grip strength. Finally, Parkkari et al 45 presented statistically significant differences (P = 0.0025) in ease of opening reported by men and women. Decreased cognitive function, as measured by the Mini-Mental-State Examination (MMSE), 30,32,40 and cognitive interpretation 31,35 impacted in a decreased ability to open medicine containers.…”
Section: Research Stream Onephysical Functionality and User Capabilitymentioning
confidence: 91%
“…Seven studies related the female gender with difficulties in opening packages. [30][31][32]34,35,38,45 For example, Atkin et al 32 found that of the 72 women in the study, 66 were unable to open all tested containers and break tablets. Of the 48 men, 28 were unable to perform the same task.…”
Section: Research Stream Onephysical Functionality and User Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…54 other study conclude that patients could manage single-dose units as least as well as the conventional eye drop bottles. 55 anyway, multidose bottles have been developed, working by either allowing the preservative filtration and posterior absorption on a porous membrane, or by using a valve system that hinders penetration of bacteria into the bottle. the aBaK ® (laboratoires théa, France) and comoD ® (ursapharm, Germany) are examples of these systems, and have been patented and commercialised with various beta-blockers such as timolol, carteolol and non antiglaucomatous compounds.…”
Section: 53mentioning
confidence: 99%